LAZAR, M. M. (Org.) Feminist Critical Discourse Analysis. Gender, Power and Ideology in Discourse. New York: Palgrave Macmillan, 2005, 251 Págs. - Silva, Luzia Rodrigues da (Cadernos de Linguagem e Sociedade, 2010)
LAZAR, M. M. (Org.) Feminist Critical Discourse Analysis. Gender, Power and Ideology in Discourse. New York: Palgrave Macmillan, 2005, 251 Págs.